The Juridical Analysis on Effectiveness of Terrorism Prevention in the Digital Era - Azis Kurnia Afandi; Ira Alia Maerani (Law Development Journal, 2021)
This study aims to analyze juridically regarding the effectiveness of preventing acts of terrorism in the digital era. The method in this research is non-doctrinal. Based on the analysis conducted, it was found that currently, the implementation of digitalization-based terrorism prevention has not been able to materialize effectively, this is shown by the increasing recruitment of members of terrorism, financing of terrorism, and the spread of terror through digital media today. Act No. 5 of 2018 in its development has not regulated the implementation of a clear terrorism prevention and the position of the protection and recovery of victims of terrorism is not yet clear and regarding the progress of information and communication technology as a means of terrorism has not been clearly regulated. In addition, it has not yet been regulated related to efforts to prevent and deal with criminal acts of terrorism. So in other words, it can be said that the proliferation of advanced methods of terrorism has not been clearly regulated in the legal politics of handling terrorism.